[2+3y] . [2+3y]
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\dfrac{-6x^3y^4+4x^4y^3}{2x^3y^3}\)
\(=\dfrac{-6x^3y^4}{2x^3y^3}+\dfrac{4x^4y^3}{2x^3y^3}\)
\(=-3y+2x\)
b: \(\dfrac{5x^4y^2-x^3y^2}{x^3y^2}=\dfrac{5x^4y^2}{x^3y^2}-\dfrac{x^3y^2}{x^3y^2}\)
\(=5x-1\)
c: \(\dfrac{27x^3y^5+9x^2y^4-6x^3y^3}{-3x^2y^3}\)
\(=-\dfrac{27x^3y^5}{3x^2y^3}-\dfrac{9x^2y^4}{3x^2y^3}+\dfrac{6x^3y^3}{3x^2y^3}\)
\(=-9xy^2-3y+2x\)
a) \(\dfrac{-6x^3y^4+4x^4y^3}{2x^3y^3}\)
\(=\dfrac{2x^3y^3\cdot\left(-3y+2x\right)}{2x^3y^3}\)
\(=-3y+2x\)
\(=2x-3y\)
b) \(\dfrac{5x^4y^2-x^3y^2}{x^3y^2}\)
\(=\dfrac{5x\cdot x^3y^2-x^3y^2\cdot1}{x^3y^2}\)
\(=\dfrac{x^3y^2\cdot\left(5x-1\right)}{x^3y^2}\)
\(=5x-1\)
c) \(\dfrac{27x^3y^5+9x^2y^4-6x^3y^3}{-3x^2y^3}\)
\(=\dfrac{-3x^2y^3\cdot-9xy^2+-3x^2y^3\cdot-3y+-3x^2y^3\cdot2x}{-3x^2y^3}\)
\(=\dfrac{-3x^2y^3\cdot\left(-9xy^2-3y+2x\right)}{-3x^2y^3}\)
\(=-9xy^2-3x+2x\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^3y^2+2x^3y^2+...+100x^3y^2\)
\(=x^3y^2\left(1+2+...+100\right)\)
\(=5050x^3y^2\)
*Chỗ 1 + 2 + ... + 100 bạn tự tính nhé!
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\((x-3y)^2-2(x-3y)(x+3y)+(x+3y)^2\)
\(=(x-3y-x-3y)^2\)
=\((-6y)^2\)
\(=36y^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) \(4x^5y^2-8x^4y^2+4x^3y^2\)
\(=4x^3y^2\left(x^2-2x+1\right)\)
\(=4x^3y^2\left(x^2-2\cdot x\cdot1+1^2\right)\)
\(=4x^3y^2\left(x-1\right)^2\)
2) \(5x^4y^2-10x^3y^2+5x^2y^2\)
\(=5x^2y^2\left(x^2-2x+1\right)\)
\(=5x^2y^2\left(x^2-2\cdot x\cdot1+1^2\right)\)
\(=5x^2y^2\left(x-1\right)^2\)
3) \(12x^2-12xy+3y^2\)
\(=3\left(4x^2-4xy+y^2\right)\)
\(=3\left[\left(2x\right)^2-2\cdot2x\cdot y+y^2\right]\)
\(=3\left(2x-y\right)^2\)
4) \(8x^3-8x^2y+2xy^2\)
\(=2x\left(4x^2-4xy+y^2\right)\)
\(=2x\left[\left(2x\right)^2-2\cdot2x\cdot y+y^2\right]\)
\(=2x\left(2x-y\right)^2\)
5) \(20x^4y^2-20x^3y^3+5x^2y^4\)
\(=5x^2y^2\left(4x^2-4xy+y^2\right)\)
\(=5x^2y^2\left[\left(2x\right)^2-2\cdot2x\cdot y+y^2\right]\)
\(=5x^2y^2\left(2x-y\right)^2\)
1: 4x^5y^2-8x^4y^2+4x^3y^2
=4x^3y^2(x^2-2x+1)
=4x^3y^2(x-1)^2
2: \(=5x^2y^2\left(x^2-2x+1\right)=5x^2y^2\left(x-1\right)^2\)
3: \(=3\left(4x^2-4xy+y^2\right)=3\left(2x-y\right)^2\)
4: \(=2x\left(4x^2-4xy+y^2\right)=2x\left(2x-y\right)^2\)
5: \(=5x^2y^2\left(4x^2-4xy+y^2\right)=5x^2y^2\left(2x-y\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(2x+3y\right)\left(2x-3y\right)-\left(2x-1\right)^2+\left(3y-1\right)^2\)
\(=4x^2-9y^2-4x^2+4x-1+9y^2-6y+1=4x-6y\)
Thay x = 1 ; y = -1 ta được :
\(4+6=10\)
=(2+3y)^2
=4+12y+9y^2
( 2 + 3y ) . ( 2 +3y )
= 2 . 2 + 2. 3y + 3y . 2 + 3y . 3y
= 4 + 6y + 6y + 9y2
= 4 + 12y + 9y2
= ( 4 + 3y )2